Transaction cost politics, institutions for commitment and rent seeking - S. Mansoob Murshed (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2001)
In developing countries, particularly in those countries that have experienced declining growth rates, institutional failure (bad policies) is closely related to development failure and growth collapses. This paper addresses the issues of commitment, compromise and rent seeking, all of which are relevant to institutional design and the formulation of optimal policies. The models in the paper are within the genre of endogenous policy formation, transaction cost politics, and models of rent seeking. I address the difficulties of credibly committing to optimal policies that involve no rent seeking by actors associated with the state, given their temptation to do so, and the general expectation that individuals associated with the government are rent seeking. I then construct a rent seeking game in the form of a contest between different individuals striving to obtain a non-divisible prize. Engaging in this contest entails a cost, which in aggregate detracts from economic production and the best use of entrepreneurial talent. I then examine the sustainability of a political compromise between competing groups, one that is eventually aimed at reducing rent seeking.
Keywords: O10; O55; 330; rent seeking; credibility; reputation; commitment; institutions; Rent Seeking; Glaubwürdigkeit; Public Choice; Institutionalismus